Supporting Learner Success: Revisiting Strategic Competence Through Developing an Inventory for Computer-Assisted Speaking Assessment - Zhang, Weiwei; Zhang, Lawrence Jun; Wilson, Aaron John (Frontiers in Psychology, 2021)
This study investigated English-as-a-foreign-language (EFL) learners' strategic competence in the computer-assisted integrated speaking tests (CAIST) through the development and validation of the Strategic Competence Inventory for Computer-assisted Speaking Assessment (SCICASA). Based on our review of the literature on the CAIST, strategic competence, and available instruments for measuring the construct, we defined EFL learners' strategic competence in the CAIST as learners' use of four metacognitive strategies: Planning, problem-solving, monitoring, and evaluating, with each of them consisting of various components. These metacognitive strategies formulated the four factors and scale items of the SCICASA under validation. An exploratory factor analysis of responses from 254 EFL students and the subsequent confirmatory factor analysis of data collected on another sample of 242 students generated 23 items under the four factors. The high validity and reliability of the SCICASA reveal that EFL learners' strategic competence operates in the forms of the four metacognitive strategies in the CAIST. This will lend some new supporting evidence for Bachman and Palmer's (2010) strategic competence model while providing implications for metacognitive instructions and test development. Concomitantly, the findings show the inventory as a valid instrument for measuring strategic competence in computer-assisted foreign/second language (L2) speaking assessment and relevant research arenas and beyond.